The practice and effects of the System of Rice Intensification (SRI) in Sri Lanka - Namara, Regassa E.; Bossio, Deborah A.; Weligamage, Parakrama; Herath, Indika (2008)
In Sri Lanka rice is grown under conditions of sub-optimal water and land availability. Thus, innovations such as the System of Rice Intensification (SRI) that can increase productivity and save resources are needed. The objective of this study was to understand how SRI was implemented on farms in Sri Lanka, and the consequences of changes in practices on: 1) input utilisation, 2) agronomic traits of rice, and 3) soil chemical properties. It was found that SRI farmers had made significant changes in their production systems: irrigations, seeding rates and herbicide usage were reduced by 24%, 85% and 95%, respectively, and plant spacing was increased by 60%. Total inputs of nitrogen, phosphorus, and potassium were similar across SRI and conventional plots, but the source of nutrients was different. Yields were variable, but significantly higher on SRI farms, soil available potassium and phosphorus were increased, and SRI plants exhibited tolerance to low moisture stress.